2019
DOI: 10.2166/wst.2019.289
|View full text |Cite
|
Sign up to set email alerts
|

Raw landfill leachate treatment using an electrocoagulation process with a novel rotating electrode reactor

Abstract: In this work, landfill leachate treatment by electrocoagulation process with a novel rotating anode reactor was studied. The influence of rotating anode speed on the removal efficiency of chemical oxygen demand (COD), total dissolved solids (TDS), and total suspended solids (TSS) of raw landfill leachate was investigated. The influence of operating parameters like leachate pH, leachate temperature, current, and inter-distance between the cathode rings and anode impellers on the electrocoagulation performance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Also, the passivation effect occurring on the electron's surface was improved or eliminated. 31 Naje et al 32 confirmed the previous results by using a rotating anode in a different configuration for the treatment of landfill leachate. The rotating anode consisted of a vertical aluminium rod with impellers, assembled with a cathode of rings, where each ring encapsulated one impeller.…”
Section: Initial Influent Concentrationmentioning
confidence: 60%
See 1 more Smart Citation
“…Also, the passivation effect occurring on the electron's surface was improved or eliminated. 31 Naje et al 32 confirmed the previous results by using a rotating anode in a different configuration for the treatment of landfill leachate. The rotating anode consisted of a vertical aluminium rod with impellers, assembled with a cathode of rings, where each ring encapsulated one impeller.…”
Section: Initial Influent Concentrationmentioning
confidence: 60%
“…The anode rotation reduced the anode passivity, but the speed needed to be adjusted to a minimum optimum to avoid the formation of small particle flocs, which are hard to collect. 32 Hamdan and El-Naas 22 proposed a rod as the sacrificial anode along with a helical cathode for the treatment of brackish groundwater to reduce the concentrations of Cr (VI) within drinking water limits and they had promising results. Goren and Kobya 33 used an iron ball anode and a cylindrical titanium cathode in an aerated EC reactor, resulting in 98.6% arsenic removal at a quite competitive operating cost of about 0.08 € m −3 at the following optimum conditions: 1.0, 26.0, 651.5, 2.0, 9.9 mg L −1 , and 10.5 min for phosphate, silicate, bicarbonate, fluoride, boron, and operating time, respectively.…”
Section: Initial Influent Concentrationmentioning
confidence: 99%
“…with several shortcomings (Hassani et al 2016). One example is adsorption, which requires a long precipitation process but is inefficient (Naje et al 2019). Electrocoagulation, on the other hand, faces a condition called sacrificial anodes phenomenon, whereby its soluble characteristic causes the need for frequent anode replacements.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, electroflotation has seen an increase in popularity due to several of its qualities, simplicity of implementation and automation (Mohtashami et al 2019), zero need for chemical addition, manageability of equipment, short retention time, low sludge generation, and longer life of electrodes (Naje et al 2019). Electroflotation works by the use of gas bubbles produced at electrodes during electrolysis of water.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, electrocoagulation with ZVI plate inevitably suffers passivation due to the formation of iron (oxyhydr)oxide passive layers on the surface of Fe(0) plates (Veluchamy et al 2017;Samir Naje et al 2019), resulting in a decrease in anodic interface potential favoring a larger faradaic current efficiency (Dubrawski et al 2015). The dissolution and passivation rate of iron were experimentally verified to strongly depend on the electrode potential, ionic strength, ionic type, and the solution pH (Lorenz et al 2002).…”
mentioning
confidence: 99%